Komunikasi Dakwah Walisongo Berlandaskan Budaya Kepada Masyarakat Jawa Pra-Islam - Musdhalifah; Istiqomalia, Yuntarti (JOM, 2024)
This study aims to explain how Walisongo implemented a culturally grounded communication strategy in delivering Islamic teachings to the pre-Islamic Javanese society. Employing a literature review method, the study examines the socio-cultural context of pre-Islamic Javanese society and the forms of da’wah communication applied by Walisongo. The data gathered from various literature sources were analyzed through an intercultural communication approach, focusing on the interactions between groups with distinct cultural backgrounds. The analysis centers on how Walisongo adapted their da’wah messages to align with local cultural practices, thereby avoiding cultural resistance.The findings of this study reveal that Walisongo adopted a communication model that was highly adaptive to Javanese cultural norms. In terms of the communicator's profile, Walisongo demonstrated an understanding of and conformity to local social norms. Meanwhile, in the aspect of verbal messaging, they employed language and symbols familiar to the local community. This process of assimilation facilitated the creation of a new cultural entity that harmonized local cultural elements with Islamic values, thereby easing the acceptance of Islam among the Javanese populace. This study highlights the critical role of culturally based da’wah approaches in successful intercultural communication, particularly within the context of Islamic propagation. The communication model used by Walisongo underscores the importance of cultural sensitivity in da’wah, which not only helps to avoid cultural conflicts but also accelerates the acceptance of religion in communities with diverse cultural backgrounds.